An Analysis of Fuel Oil Sloshing in Partially Filled Cargo Tanker Trucks under Cornering Conditions Using Various Baffle Systems - Woinshet Siraye; Alemayehu Wakjira; Ramesh Babu Nallamothu (Journal of Engineering)
Ethiopia imports all fuel and crude oils from abroad at high cost, and transportation of these fluids has been carried out by using various capacity of road transportation heavy-duty truck vehicle. Most tanker truck accidents happen during turning because of the fluid splashing in partially loaded tanks and of the uniqueness of the carrying liquids. This is a result of the fact that current baffle configurations are effective at reducing sloshing when braking or accelerating but ineffective at doing so when turning. Consequently, the primary goal of this thesis work is to investigate how different baffle systems affect lateral sloshing reduction. In this work, the optimal baffle configuration and its arrangements for modified oval tanks at 50% and 80% fill levels were tried, and the dynamic analysis of tanker trucks was researched. The tanker truck and baffle system are designed in CATIA V5 for the numerical analysis, and the CFD study is completed in ANSYS Fluent 2021. R2 and the dynamic analysis are carried out in ANSYS LS-DYNA to study the stability of truck. The computational simulation is carried out as a tank with eight types of baffle systems such as existing baffles (TB), TB with BMLB, UMLB, CLB, 2HLB, 2VHLB, 4HLB, and 4VHLB with similar meshing resolution, similar turbulence modeling, similar boundary conditions, and also similar solution strategies. Transverse baffles with bottom-mounted four holes longitudinal baffle with hole-varying position (4VHLB) are discovered to be the best baffle type after evaluating all baffle designs. This suggests that the quantity of sloshing is reduced as the number of holes with small diameters increases. Maximum lateral force and roll moment are reduced by the most, by 47.76% and 58.66%, respectively, at 50% fill level and by 58.08% and 22.52%, at 80% fill level. Consequently, the case tanker truck’s use of this revised design baffle will be crucial for enhancing rollover stability while cornering.